Using the NHS sustainability framework to understand the activities and resource implications of Canadian nursing guideline early adopters. Issue 11 (4th September 2012) - Higuchi, Kathryn Smith; Downey, Angela; Davies, Barbara; Bajnok, Irmajean; Waggott, Melissa
<x xml:space="preserve">Abstract</x> Aims and objectives. To examine the activities and resource implications for the initial cohort of healthcare organisations involved in the introduction of multiple nursing guidelines. Background. The Best Practice Spotlight Organization initiative was launched in 2003 as part of the Registered Nurses' Association of Ontario's Best Practice Guidelines programme. While previous research has evaluated improvements in patient care and outcomes, there has been limited research from an organisational perspective on the activities conducted to introduce nursing guidelines. Design. Secondary analysis of retrospective narrative data. Methods. We conducted a content analysis of the 2004–2006 annual reports from the seven participating sites. We used both deductive and inductive approaches to categorise the guideline implementation activities and their resource implications. Results. All sites reported implementing multiple guidelines (four to nine guidelines per site) and used a wide range of implementation activities that clearly addressed nine of the 10 NHS Sustainability dimensions. The dimension not reported was benefits beyond helping patients. All sites established steering committees that involved staff and senior leaders, reviewed selected guidelines and recommendations, reviewed existing policies and procedures and developed new policies and procedures, recruited champions or peer mentors, applied for additional external funding to support activities, developed relationships with external clinical partners, included guideline implementation in orientation, developed intra‐agency web‐based and print communications for the project, and evaluated practice changes. For each of these activities, the sites reported expenditures and resource usage. Conclusions. The organisational processes used for the introduction of new nursing guidelines in Canada are remarkably consistent with factors identified by leaders and change agents in the UK who developed the NHS Sustainability Model. Relevance to clinical practice. A multidimensional framework for sustainability is useful for planning successful guideline implementation across an organisation. Examples of specific activities and resource implications for organisational change are provided.